2008
DOI: 10.1152/ajpheart.01280.2007
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of fish oil and flaxseed oil on cardiac allograft chronic rejection in rats

Abstract: Othman RA, Suh M, Fischer G, Azordegan N, Riediger N, Le K, Jassal DS, Moghadasian MH. A comparison of the effects of fish oil and flaxseed oil on cardiac allograft chronic rejection in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Many controlled intervention studies have shown the lipidlowering effect of flaxseed oil [20][21][22][23]. In our study, the plasma and hepatic lipid levels further decreased and cholesterol secretion of rats increased in CFO group when compared with HRFO group In order to retain the most quantity of natural micronutrients, some new oil processing technology and pre-treatment methods have appeared, and studies about the effect of oil quality obtained by different crushing and refining procedures on lipid metabolism were reported.…”
Section: Discussionmentioning
confidence: 52%
“…Many controlled intervention studies have shown the lipidlowering effect of flaxseed oil [20][21][22][23]. In our study, the plasma and hepatic lipid levels further decreased and cholesterol secretion of rats increased in CFO group when compared with HRFO group In order to retain the most quantity of natural micronutrients, some new oil processing technology and pre-treatment methods have appeared, and studies about the effect of oil quality obtained by different crushing and refining procedures on lipid metabolism were reported.…”
Section: Discussionmentioning
confidence: 52%
“…Vegetable leaf and flaxseed oil are notable dietary sources of ALA. Flaxseed oil is also beneficial on hyperlipidemia, hepatic steatosis, and atherogenesis in rodents. However, it remains inconclusive whether fish oil is more effective than flaxseed oil in preventing atherosclerosis. Some studies have demonstrated that fish oil possesses more profound benefits than flaxseed oil to suppress inflammation, prevent pressure overload-induced cardiac dysfunction, and reduce atherogenesis in rodent models. , However, other two studies have reported that both flaxseed oil and fish oil are comparable in reducing plasma total cholesterol (TC) in C57BL/6 mice fed a high-cholesterol diet, and exert similar blood pressure-lowering and anti-inflammatory effects in rats after heart transplantation. , Interestingly, it has been shown that fish oil raises the blood pressure and wall thickness in the left ventricle, whereas flaxseed oil remains neutral to affect the diastolic function in ApoE –/– mice …”
Section: Introductionmentioning
confidence: 99%
“…28,29 However, other two studies have reported that both flaxseed oil and fish oil are comparable in reducing plasma total cholesterol (TC) in C57BL/6 mice fed a high-cholesterol diet, and exert similar blood pressure-lowering and anti-inflammatory effects in rats after heart transplantation. 25,30 Interestingly, it has been shown that fish oil raises the blood pressure and wall thickness in the left ventricle, whereas flaxseed oil remains neutral to affect the diastolic function in ApoE −/− mice. 31 The present study was conducted (i) to investigate whether flaxseed oil or fish oil was able to suppress the TMAOexacerbated atherogenesis and (ii) to compare the relative potency of fish oil with that of flaxseed oil against TMAOaggravated inflammation, cholesterol dysregulation, and modulation in gut microbiota in ApoE −/− mice fed a Western high fat diet (WD).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Flaxseed oil also reduces TG and total cholesterol in rats (Prasad, 2000). In another study, flaxseed oil caused a greater increase in HDL levels compared with fish oil (Othman et al, 2008). A study showed that daily consumption of 2-6 tablespoons of flaxseed oil (crushed or powdered) can reduce total cholesterol (10-20%) and LDL (6-9%) in healthy subjects (Cunnane et al, 1995), patients with high cholesterol (Bierenbaum et al, 1993), and postmenopausal women (Lucas et al, 2002).…”
Section: Discussionmentioning
confidence: 98%